Difference of perceived effort index in reserve as a self-regulation method compared to objective effort methods: a systematic review - Yáñez Sepúlveda, Rodrigo; Monsalves-Álvarez, M; Cortés Roco, Guillermo; Mateluna Núñez, Cristián Andrés; Tuesta Roa, Marcelo; Alvear-Órdenes, Ildefonso; Vásquez Mercado, Sebastian; Zavala Crichton, Juan Pablo; Troncossi, Angelo (Retos (Madrid), 2024)
The use of rate of perceived effort scales (RPE) based on reserve repetitions (RIR) can be a complement to absolute methods, such as 1 maximum repetition (1RM), the percentage variable with respect to 1RM (xRM), and the average concentric velocity (ACV), optimizing control of training intensity. This study aimed to evaluate the validity of using a subjective RPE-RIR effort scale as a self-regulation tool with respect to quantifying the intensity of the training load. We perform a systematic search in PubMed, WOS, and Scopus databases. 2,271 articles were reviewed, of which 7 met the eligibility criteria. These studies involved 147 subjects trained in strength (novices, experienced professionals, and powerlifters), who responded to the implementation of protocols that quantify the subjective and objective load intensity (RPE-RIR relationship and objective load intensity, mean speed - 1RM/xRM). There are strong correlations between the variables in the RPE-RIR study/ Average concentric velocity (r = 0.90 - 0.92; r = -0,98 to -1,00; EL: r = 0.85/ r = -0.88, NL: r = 0.85/ r = -0.77), RPE-RIR/1RM (r = 0.88 to 0.91). The main conclusions of this systematic review regarding methods and means of quantifying objective and subjective intensity of training load indicate a strong correlation between RPE-RIR (as a subjective method) and ACV and 1RM/xRM (as an objective method), especially in inexperienced populations. However, these findings should be considered individually, given the differences between protocols and movements analyzed and the limited analysis of novice populations. El uso de escalas de tasa de esfuerzo percibido (RPE) basadas en repeticiones de reserva (RIR) puede ser un complemento a los métodos absolutos, como 1 repetición máxima (1RM), la variable porcentual con respecto a 1RM (xRM) y la velocidad concéntrica media (VCM), optimizando el control de la intensidad del entrenamiento. El objetivo de este estudio fue evaluar la validez del uso de la escala de esfuerzo subjetiva RPE-RIR como herramienta de autorregulación con respecto a los métodos de cuantificación de la intensidad de la carga de entrenamiento. Realizamos una búsqueda sistemática en las bases de datos PubMed, WOS y Scopus. Se revisaron un total de 2.271 artículos, de los cuales 7 cumplieron con los criterios de elegibilidad. En estos estudios participaron 147 sujetos entrenados en fuerza (novatos, experimentados, profesionales, levantadores de pesas), que respondieron a la implementación de protocolos que cuantifican la intensidad de carga subjetiva y objetiva (relación RPE-RIR e intensidad de carga objetiva, velocidad concéntrica media - 1RM/xRM). Se encontraron fuertes correlaciones entre las variables del estudio RPE-RIR/ Velocidad concéntrica media (r = 0,90 - 0,92; r = -0,98 a -1,00; EL: r = 0,85/ r = -0,88, NL: r = 0,85/ r = -0,77), RPE-RIR/1RM (r = 0,88 a 0,91). Las principales conclusiones de esta revisión sistemática en relación con los métodos y medios para cuantificar la intensidad objetiva y subjetiva de la carga de entrenamiento indican una fuerte correlación entre el RPE-RIR (como método subjetivo) y el VCM y 1RM/xRM (como método objetivo), especialmente en poblaciones inexpertas. Sin embargo, estas conclusiones deben considerarse individualmente, dadas las diferencias entre protocolos y movimientos analizados y el análisis limitado de poblaciones noveles.